Prevalence of maxillary canine impaction in dental and oral hospital (RSGM) Syiah Kuala University Banda Aceh, Indonesia - Kemala HAYATI; Teuku Ahmad ARBI; Khalid MUBARAK (Journal of Syiah Kuala Dentistry Society, 2021)
ABSTRACT Impacted teeth are a common phenomenon in dentistry. These impacted teeth could lead to severalproblems in the oral environment, such as an oral cyst. The maxillary canine is one of the teeth that has undergoneimpaction. Various studies were conducted to search for the prevalence of maxillary canine impaction. This studyaims to know the majority of maxillary canine impaction in Dental and Oral Hospital Syiah Kuala University BandaAceh. This study method was descriptive by collecting the panoramic radiograph's secondary maxillary canineimpaction. The result showed that from 1 408 panoramic radiographs taken in Radiology Installation of Dental andOral Hospital Syiah Kuala University Banda Aceh, there were 38 panoramic radiographs with maxillary canineimpaction (2.7%) and 1,370 panoramic radiographs without maxillary canine impaction (97.3%). Based on gender,the prevalence of Maxillary canine impaction in males was 2.2%, and for females was 3.0%. Based on the location ofMaxillary canine impaction, unilaterally was 81.6% and bilaterally was 81.4%. Based on age, the most prevalentmaxillary canine impaction was in the age group 15-24 years which is 57.9%KEYWORDS: maxillary canine impaction, panoramic radiograph